Research focus and trends of the association between gut microbiota and neuroinflammation - Wu, Shan; Chen, Nanjie; Wang, Chuanchi; So, Kwok-Fai (Frontiers in Microbiology, 2025)
BackgroundThe interaction between the gut microbiota and neuroinflammation plays a crucial role in the pathogenesis of many diseases, particularly neurodegenerative diseases, and has become one of the focal points of research in recent years. Despite the large number of related studies, there is currently a lack of comprehensive analysis and prediction of these data to drive the field forward. This study aims to systematically analyze the clinical practices and research hotspots of the underlying mechanisms in this field using bibliometric and visualization methods, and to explore the future development pathways.MethodsCiteSpace, VOSviewer, GraphPad Prism and other software were used to analyze 1,404 studies on gut microbiota and neuroinflammation collected by the core of the Web of Science since 2000, to visually present the collaborative network between literatures, structure of authors and countries, co-occurrence of keywords, emerging reference literature, and research hotspots.ResultsFrom 2000 to 2024, the number of related papers on this topic showed an overall upward trend, and the annual citation peaked in 2020, with significant contributions from China and the United States. Research focused on the relationship between gut microbiota and neuroinflammation, with a particular emphasis on investigating the mechanisms of the microbiota-gut-brain axis through both basic and clinical research. Treatment strategies include probiotic therapy, fecal microbiota transplantation and traditional Chinese medicine.ConclusionThis study comprehensively reviews the research progress on the association between gut microbiota and neuroinflammation, and discusses the current research focus and frontier directions of this relationship, so as to provide reference for the development of this field.